Pengaruh Kualitas Pelayanan Terhadap Kepuasan Mahasiswa (Studi Pada Perpustakaan Fakultas Ekonomi Dan Bisnis Unimal - Widyana Verawaty Siregar; Sapna Biby; Murdani Murdani (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2020)
This study aims to examine the effect of physical evidence, reliability, responsiveness, assurance and empathy on consumer satisfaction (Studies in the Library of the Faculty of Economics and Business, University of Malikussaleh). The data used are primary data by using accidental sampling method. The sample used was 142 visitors to the Library of the Faculty of Economics and Business, University of Malikussaleh. The results of the study partially show that the variables of Physical Evidence, Responsiveness, Assurance and Empathy have a significant effect on the variable of Customer Satisfaction (Studies in the Library of the Faculty of Economics and Business, University of Malikussaleh). While the reliability variable does not have a significant affect on to consumer Satisfaction variable (Study at the Library of the Faculty of Economics and Business, University of Malikussaleh). Simultaneously the results of this study indicate that physical evidence, reliability, responsiveness, assurance and empathy have a significant effect on the dependent variable of consumer satisfaction (Studies in the Library of the Faculty of Economics and Business, University of Malikussaleh). Keywords: Physical Evidence, Reliability, Responsiveness, Guarantee of Empathy and Customer Satisfaction